New Heuristic Algorithm for Dynamic Traffic in Wdm Optical Networks [Nuevo Algoritmo Heurístico Para Tráfico Dinámico en Redes Ópticas Wdm] - Travieso-Torres, J; Travieso-Torres, J; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Revista Ingenieria e Investigacion - Editorial Board, 2015)
This paper presents the results from the simulation of Snake One, a new heuristic algorithm, and the comparison made between three heuristic algorithms: Genetic Algorithms, Simulated Annealing, and Tabu Search, using blocking probability and network utilization as standard indicators. The simulation exercise was conducted on WDM NSFNET under dynamic traffic conditions. The results show a substantial decrease of blocking. However, this causes a relative network utilization growth. There are also load intervals which lead to performance improvement, decreasing the number of blocked requests. © 2015, Revista Ingenieria e Investigacion - Editorial Board. All rights reserved.